TRANSITIVITY ANALYSIS OF THE VIETNAMESE ECONOMIC CONTRACTS FROM THE PERSPECTIVE OF SYSTEMIC FUNCTIONAL GRAMMAR - Linh, Nguyen Thi Nhat (VNU Journal of Foreign Studies; Vol 37 No 6, 2021)
The economic contract is a typical type of discourse that depends on the agreement between parties. This paper adopted the theoretical framework of Systemic Functional Grammar (SFG) to carry out a transitivity analysis of the ideational function in the Vietnamese economic contract in order to explore the features of this genre, a type of legal discourse. In the economic contract, there are six processes, among which the material process and existential process are dominantly used while the relational process, mental process, behavioral process, and verbal process, each just accounts for the small percentage. These processes are employed in order to express the parties’ experience through legislation of rights, duties, obligation, remedies that they reach during the negotiation. The dominance of such specific processes reflects some features of legal discourse such as conciseness, clearness, exactness.